2016
DOI: 10.1016/j.techfore.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Individual information security, user behaviour and cyber victimisation: An empirical study of social networking users

Abstract: While extant literature on privacy in social networks is plentiful, issues pertaining to information security remain largely unexplored. This paper empirically examines the relationship between online victimisation and users' activity and perceptions of personal information security on social networking services (SNS). Based on a survey of active users, we explore how behavioural patterns on social networks, personal characteristics and technical efficacy of users impact the risk of facing online victimisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 91 publications
5
79
0
1
Order By: Relevance
“…4). Yet, among many studies [12,23,24,26,30] that have empirically tested the impact of the Internet and computer knowledge in preventing users from getting phished, only two studies [12,30] found this relation to be significant. This contradictory result might imply that user internet or computer knowledge is a very general concept whose impact on safe or risky behaviour could be hard to measure.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4). Yet, among many studies [12,23,24,26,30] that have empirically tested the impact of the Internet and computer knowledge in preventing users from getting phished, only two studies [12,30] found this relation to be significant. This contradictory result might imply that user internet or computer knowledge is a very general concept whose impact on safe or risky behaviour could be hard to measure.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Notably, some research found no correlation between perceived risk and users' behaviour toward either email phishing [30], or social network victimisation [26]. This contradicts the view that the individual's perceived severity of negative consequences predicts their detection or avoidance behaviour of online threats.…”
Section: Perceptual-related Attributesmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the fun, useful and innovative nature of social media frequently makes the users to ignore various risks about revealing their personal and social information online. Several studies [47,1,104] reported that online users are becoming more and more conscious and protective about their privacy. A study conducted in 2005 [47] used a sample of 4540 users who shared identifiable names, phone numbers, personal images and characteristics (e.g.…”
Section: Privacy Of Online Social Networkmentioning
confidence: 99%